Curative Efficacy of Yellow Root (Arcangelisia flava) Extract Against Aeromonas hydrophila Bacterial Infection in Climbing Perch (Anabas testudineus) - Maryani, Maryani; Monalisa, Shinta Sylvia; Rozik, Mohamad; Elvince, Rosana (Universitas Gadjah Mada, 2025)
Yellow root (Arcangelisia flava) demonstrates potential for combating bacterial infections in aquaculture due to its secondary metabolite content, which includes flavonoids, terpenoids, and protoberberine alkaloids. This study aimed to evaluate the efficacy of yellow root extract as a curative agent against Aeromonas hydrophila infection in Climbing Perch (Anabas testudineus). The method employed was an in vivo study using immersion treatments of yellow root extract at concentrations of 200, 400, and 600 mg/L, alongside a control (0 mg/L). Observations were conducted for 10 days post-infection and treatment, covering clinical symptoms and Survival Rate (SR). Prior to treatment, the fish exhibited clinical symptoms characteristic of A. hydrophila, such as red spots and exophthalmia. The results indicated that water quality parameters (temperature 26.4–27.1°C, pH 6.8–7.1, DO 3.28–3.47 mg/L) remained within optimal and stable ranges. In the extract treatment groups (B, C, and D), significant recovery was observed starting from day 3, achieving a 100% SR by day 10. In contrast, the control group (A) only attained an SR of 26.6%. This curative success is attributed to the mechanism of action of active compounds, which disrupt bacterial membranes and inhibit metabolism. It is concluded that A. flava extract is effective as a natural alternative treatment for bacterial infections in Climbing Perch.